Characteristics, mortality and outcomes at transition for adolescents with perinatal HIV infection in Asia. (31st July 2018) - Bartlett, Adam W.; Truong, Khan Huu; Songtaweesin, Wipaporn Natalie; Chokephaibulkit, Kulkanya; Hansudewechakul, Rawiwan; Ly, Penh Sun; Lumbiganon, Pagakrong; Sudjaritruk, Tavitiya; Nguyen, Lam Van; Do, Viet Chau; Kumarasamy, Nagalingeswaran; Nik Yusoff, Nik Khairulddin; et al.
Abstract : Objectives: The aim of this study was to describe characteristics of perinatally HIV-infected adolescents (PHIVAs), factors associated with mortality, and outcomes at transition. Design: Ongoing observational database collating clinical data on HIV-infected children and adolescents in Asia. Methods: Data from 2001 to 2016 relating to adolescents (10–19 years) with perinatal HIV infection were analysed to describe characteristics at adolescent entry and transition and combination antiretroviral therapy (cART) regimens across adolescence. A competing risk regression analysis was used to determine characteristics at adolescent entry associated with mortality. Outcomes at transition were compared on the basis of age at cART initiation. Results: Of 3448 PHIVA, 644 had reached transition. Median age at HIV diagnosis was 5.5 years, cART initiation 7.2 years and transition 17.9 years. At adolescent entry, 35.0% had CD4 + cell count less than 500 cells/μl and 51.1% had experienced a WHO stage III/IV clinical event. At transition, 38.9% had CD4 + cell count less than 500 copies/ml, and 53.4% had experienced a WHO stage III/IV clinical event. Mortality rate was 0.71 per 100 person-years, with HIV RNA ≥1000 copies/ml, CD4 + cell count less than 500 cells/μl, height-for-age or weight-for-age z -score less than −2, history of a WHO stage III/IV clinical event or hospitalization and at least second cART associated with mortality. For transitioning PHIVA, those who commenced cART age less than 5 years had better virologic and immunologic outcomes, though were more likely to be on at least second cART. Conclusion: Delayed HIV diagnosis and cART initiation resulted in considerable morbidity and poor immune status by adolescent entry. Durable first-line cART regimens to optimize disease control are key to minimizing mortality. Early cART initiation provides the best virologic and immunologic outcomes at transition.